C60 hexakisadducts with an octahedral addition pattern - A new structure motif in organic chemistry - Hirsch, Andreas; Vostrowsky, Otto (European Journal of Organic Chemistry, 2001)
Hexakisadducts, with T-symmetrical addition patterns, of C buckminsterfullerene can be obtained by means of cyclo-additions, solid state reactions and nucleophilic cyclopropanations, including a variety of template and tether techniques. C - or a precursor adduct - serves as a core building block for elaboration into a pseudo-octahedral architecture; an aesthetically pleasing structure motif unique in organic chemistry. The fullerene core can be systematically embellished with one or more different types of addends, giving rise to the formation of uniform or mixed hexakisadducts, respectively. The regioselective exohedral chemistry of C may serve to provide soluble fullerene derivatives, lipofullerenes, dendrimers, charge-transfer systems, globular amphiphiles and compounds with interesting chemical, physical, biological and material properties.